Facile dip-coating assisted preparation of reduced graphene oxide-copper oxide nanocomposite thin films on aluminum substrate for solar selective absorber - Murugesan N.; Suresh S.; Kandasamy M.; Murugesan S.; Pugazhenthiran N.; Venkatesh V.P.; Balachandar B.K.; Karthick Kumar S.; Ansari M.N.M. (Elsevier B.V., 2024)
Reduced graphene oxide integrated copper oxide nanocomposite thin film (rGO-CuO NC TF) solar selective absorber coatings were devised on aluminum substrate using dip-coating procedure. The prepared coatings were subjected to characterization by scanning electron microscopy, X-ray diffractometry, energy-dispersive X-ray spectroscopy, X-ray photoelectron spectroscopy, PL spectroscopy, UVvisNIR spectrophotometer, Emissometer and Raman spectroscopy. XRD and Raman analyses disclosed presence of mono-phase with highly crystalline monoclinic structured CuO in the rGO-CuO NC TFs. The SEM images revealed grain-like morphology of CuO, which are randomly distributed on rGO sheets. EDX and XPS investigations confirmed presence of anticipated chemical constituents and chemical composition, respectively in the NC TFs. The rGO-CuO NC TF with 1.0 wt% GO disclosed absorptance (?) of 79.92% and emittance (?) of 4.2% with a highest selectivity (?) of 19.03 that suggests its promising prospect for solar absorber coating in solar thermal devices. 2023 Elsevier B.V.